Local-to-local electoral connections for migrants: the association between voting rights in the place of origin and the propensity to vote in the place of residence. Issue 1 (2nd January 2023) - Piccoli, Lorenzo; Ruedin, Didier
ABSTRACT: The study of transnationalism raises important questions about the effects of political rights that international migrants enjoy in different places. We contribute to this debate asking the following question: Do international migrants who retain voting rights in the place of origin have a greater propensity to vote in the local elections of the country of residence than those who do not retain such rights? We analyse individual-level survey data of voting turnout in the 2015 municipal elections in Geneva, combined with information about voting rights in the municipality of origin ( local-to-local connections ) and in the country of origin ( national-to-local connections ). We find statistical effects of national-to-local connections only in models with no additional control variables, while the statistical effects of local-to-local connections are strong and robust. This points to an association between retaining voting rights in the municipality of origin and the propensity to vote in the local elections in the country of residence. We suggest that local-to-local electoral connections are produced by spill-over: By actively pursuing the diaspora, political parties, unions, and local electoral commissions act as vehicles of greater electoral participation not only in migrants' municipality of origin, but also in their municipality of residence.